Clinical pattern and progression of ulcerative proctitis in the Japanese population: a retrospective study of incidence and risk factors influencing progression. (March 2016) - Anzai, H.; Hata, K.; Kishikawa, J.; Ishii, H.; Nishikawa, T.; Tanaka, T.; Tanaka, J.; Kiyomatsu, T.; Kawai, K.; Nozawa, H.; Kazama, S.; Yamaguchi, H.; et al.
Abstract: Aim: The rate of extension of proctitis in Western countries has been reported, but no data regarding long‐term follow‐up have been described for the Japanese population. Additionally, patients with long‐standing or extensive ulcerative colitis have an increased risk for developing colorectal cancer. This study evaluated both the rate of extension of the disease and the development of neoplasia among patients with an initial diagnosis of ulcerative proctitis. Method: We retrospectively investigated the medical charts of patients with proctitis from 1979 to 2014. The primary focus of this research was the extension of the inflammatory area. The secondary focus included risk factors for disease extension and the development of neoplasia. Results: Sixty‐six patients satisfied the inclusion criteria. Proximal extension of the disease occurred in 34 patients: 19 patients had left‐sided colitis and 15 had pancolitis. According to a multivariate analysis, disease extension was significantly higher in patients with disease onset before 25 years of age ( P ‐value = 0.043). The cumulative rates of disease extension at 10 and 20 years were 33.8% and 52.2%, respectively. Three patients were diagnosed with dysplasia during follow‐up, all of whom experienced disease extension before the development of dysplasia. Conclusion: The rate of extension of ulcerative colitis in the Japanese population was comparable to that in Western countries. A younger age of disease onset was associated with disease extension. Extension of proctitis may be associated with an increased risk of colorectal cancer.